Pengaruh Kualitas Layanan, Kualitas Produk dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan di Sentra Kuliner Pesantren Tebuireng - Wahid, Iqbal Billy (Jurnal Ilmu Manajemen, 2023)
Sustainability in business is one of the things we can do to save the earth. On the other hand, many companies still need to implement sustainability in their business. This research aims to determine the influence of environmental concern and perceived environmental knowledge on environmentally friendly purchasing intentions through environmental attitudes as a mediating variable. This research uses a purposive sampling method, using 100 respondents. Using a path analysis model with AMOS software. The results of this research show that there is an influence between perceived environmental knowledge and environmental attitudes on environmentally friendly purchasing intentions. However, this research did not find any influence of environmental concern on environmentally friendly purchasing intentions because environmentally friendly product consumption patterns have not yet been formed. This research is useful for researchers and beauty brands in Indonesia, especially The Body Shop Refill Station, to pay attention and care about the importance of perceived environmental knowledge and environmental attitudes for consumers. Even though consumers have a high level of environmental awareness, this does not guarantee that they will have the intention to purchase environmentally friendly The Body Shop refill station products.